2006
DOI: 10.1096/fj.05-5576fje
|View full text |Cite
|
Sign up to set email alerts
|

Coding region paraoxonase polymorphisms dictate accentuated neuronal reactions in chronic, sub‐threshold pesticide exposure

Abstract: Organophosphate pesticides (OPs), known inhibitors of acetylcholinesterase (AChE), are used extensively throughout the world. Recent studies have focused on the ACHE/PON1 locus as a determinant of inherited susceptibility to environmental OP exposure. To explore the relationship of the corresponding gene-environment interactions with brain activity, we integrated neurophysiologic, neuropsychological, biochemical, and genetic methods. Importantly, we found that subthreshold OP exposure leads to discernible phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 58 publications
2
25
1
Order By: Relevance
“…activity toward diazoxon in both cases and in controls. Also, Browne et al 70 studied workers with exposure to OP and found a significant decrease of AChE and a compensatory increase in paraoxonase as a result of such exposure. According to the authors, the serum levels of these enzymes are the result of a complex interaction between genetic (genotype) and environmental (exposure to chemicals) factors and the locus determining AChE/PON1 represents an innate susceptibility to OP.…”
Section: Phenotype and Genotype Of Pon1mentioning
confidence: 99%
“…activity toward diazoxon in both cases and in controls. Also, Browne et al 70 studied workers with exposure to OP and found a significant decrease of AChE and a compensatory increase in paraoxonase as a result of such exposure. According to the authors, the serum levels of these enzymes are the result of a complex interaction between genetic (genotype) and environmental (exposure to chemicals) factors and the locus determining AChE/PON1 represents an innate susceptibility to OP.…”
Section: Phenotype and Genotype Of Pon1mentioning
confidence: 99%
“…Evidence from epidemiology indicate that chronic organophosphorus exposure would lead to the impairments of neurocognitive functions 12, 13, 14, 15. Thus, we suggested that chronic organophosphorus exposure might induce cerebrovascular dysfunctions and sequential cognitive impairments.…”
Section: Introductionmentioning
confidence: 75%
“…Carriers constitutively overexpress AChE (Shapira et al, 2000), but are unable to further increase AChE expression and specifically induce the AChE-R variant to counteract ACh hyperexcitability; this could result in disturbed neurogenesis, in turn predisposing to posttraumatic stress disorder which is thought to result at least in part from defective neurogenesis (Vermetten et al, 2003). Correspondingly, carriers of the above polymorphisms demonstrate state anxiety and acute electroencephalographic reactions to insecticide exposure (Browne et al, 2006).…”
Section: Discussionmentioning
confidence: 99%